Quantitative assessment of the associations between MTR and MTRR gene polymorphisms and glioma risk - Xu Chen; Yanping Yao; Xi Wang; Jun Qiu (Discover Oncology)
Abstract Purpose Previous research on the correlation between methionine synthase (MTR) and methionine synthase reductase (MTRR) gene polymorphisms and the susceptibility to glioma has yielded varied results. This study aims to elucidate the potential impact of MTR and MTRR polymorphisms as contributing factors in the development of glioma. Patients and methods A comprehensive review of the relevant literature was conducted across several major databases, encompassing records from their inception through April 2025. The data were then synthesized using meta-analysis techniques. Results No significant associations between the MTR rs1805087 polymorphism and glioma risk were identified under any genetic model across all populations (all p > 0.05). However, we found that MTRR rs1801394 polymorphism was significantly associated with the glioma risk for Asian population (all p < 0.05). Conclusion In conclusion, our study indicates that the MTRR rs1801394 polymorphism serves as a protective factor in India populations but does not affect glioma risk in Caucasian population and Chinese population, which can be used as biomarkers for predicting glioma risk and can serve as targets for personalized treatments of glioma.